The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/ijerph15051019
|View full text |Cite
|
Sign up to set email alerts
|

Quorum Sensing versus Quenching Bacterial Isolates Obtained from MBR Plants Treating Leachates from Municipal Solid Waste

Abstract: Quorum sensing (QS) is a mechanism dependent on bacterial density. This coordinated process is mediated by the synthesis and the secretion of signal molecules, called autoinducers (AIs). N-acyl-homoserine lactones (AHLs) are the most common AIs that are used by Gram-negative bacteria and are involved in biofilm formation. Quorum Quenching (QQ) is the interference of QS by producing hydrolyzing enzymes, among other strategies. The main objective of the present study was to identify QS and QQ strains from MBR wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 81 publications
0
17
0
Order By: Relevance
“…Many QS signal molecule-degrading microbes have been found in nature, including Gordonia sp. (Soler et al, 2018), Bacillus sp. (Dong et al, 2002;Lee et al, 2002;Ulrich, 2004;Soler et al, 2018;Bhatt et al, 2020), Streptomyces sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many QS signal molecule-degrading microbes have been found in nature, including Gordonia sp. (Soler et al, 2018), Bacillus sp. (Dong et al, 2002;Lee et al, 2002;Ulrich, 2004;Soler et al, 2018;Bhatt et al, 2020), Streptomyces sp.…”
Section: Discussionmentioning
confidence: 99%
“…(Soler et al, 2018), Bacillus sp. (Dong et al, 2002;Lee et al, 2002;Ulrich, 2004;Soler et al, 2018;Bhatt et al, 2020), Streptomyces sp. (Park et al, 2005;Devaraj et al, 2017), Micromonospora sp.…”
Section: Discussionmentioning
confidence: 99%
“…Since QQ strategies do not interfere directly with bacterial growth, the probabilities of inducing tolerance or resistance against these mechanisms are lower 37,38 . Previous studies have already reported the successful approach of using QS inhibitors to control different types of bacterial biofilms 35,[39][40][41][42] . Therefore, the confirmation of a possible role of AHL-type QS signals in dental plaque formation would open new perspectives in the prevention and treatment of oral diseases.…”
mentioning
confidence: 99%
“…Over the last years, interfering with QS bacterial communication systems has been proposed as a promising mechanism to prevent the development of different types of bacterial biofilms [ 11 , 12 , 13 , 14 , 15 ]. Commonly, the term “quorum quenching” (QQ) refers to the enzymatic inactivation of QS processes [ 16 ], while the more general term “quorum sensing inhibition” (QSI) is preferred to describe the chemical disruption of the cell-to-cell communication system caused by QS inhibitory compounds [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Using QQ enzymes that can degrade the AHLs produced by Gram-negative bacteria has been suggested as a novel anti-biofouling strategy [ 25 , 26 , 27 ], and a few studies have evaluated the effect of QQ enzymes on the ecology of multispecies biofilms [ 14 , 28 , 29 , 30 ]. QQ strategies have been successfully applied to control biofouling in membrane bioreactors (MBRs) for wastewater treatment [ 11 , 15 ] and to reduce biocorrosion [ 28 ], as they are associated with deep changes in the microfouling community [ 28 ]. This effect could be observed even in in vitro oral biofilm models dominated by Gram-positive species [ 14 ].…”
Section: Introductionmentioning
confidence: 99%